Deutsche Literatur nach dem Dritten Reich. Die fünfziger Jahre im „toten Winkel“ der Geschichte - Karolak, Czesław (Wydawnictwo Naukowe UAM, 1990)
The article takes up some aspects of historiosophic attitudes of some West German writers in the 50's. The research material are mostly non-literary utterances of the authors - their opinions and so on. As a result of research work the author showed that the central phenomenon influencing historiosophic attitudes of writers of those times was the suggestion of transferring attitudes towards the society of the Third Reich to the post war years. The authors clearly referred to the principle of “double negation” shown in the rejection of Nazi ideology and in opposition attitudes and preferring as “the third road” an attempt to take “the middle position”. This attitude being a (belated) simulation of the picture of “Germany of moderation and humanism” had an important influence on the attitude of writers towards history: one can see a distinct attempt to “avoid all costs” of taking up and explaining historical phenomena.